Green care in psychiatry. (February 2021) - Cuthbert, Sharon; Kellas, Alan; Page, Lisa A.
Summary: Engagement with natural environments is associated with improved health and well-being in the general population. This has implications for mental healthcare. Implementation of targeted nature-based interventions (green care) meets recovery needs and would enable research to develop, clarifying what works best for whom.